Anticariogenic Activity of Steroid Phytocompound Isolated from Acmella calva (DC.) R.K. Jansen - Shanthi, Dr. P. (Asian Journal of Pharmaceutics (AJP), 2023)
Aim: The phytocompound Stigmast – 5 – En - 3 Beta – Ol isolated and characterized through spectral studies was analyzed for its anticariogenic activity through disc diffusion method and in silico analysis. Materials and Methods: Anticariogenic activity was carried against dental caries causing microbes such as Streptococcus mutans, Streptococcus salivarius, Streptococcus sobrinus, and Staphylococcus aureus at different concentration (20, 40, 60, 80, 100,120, 140, and 160 as robes such as Autonomous), Affiliated to Bharathidasan University, Tiruchirappalli against S. mutans. In in silico analysis, the molecular docking of phytocompound was analyzed against eight proteins of four pathogens which were retrieved from PDB database. Results and Discussion: The phytocompound Stigmast – 5 – En - 3 Beta – Ol showed good response against all proteins. Among these, the highest ligand and protein interaction was noticed in 3AIE protein of S. mutans. The steroid compound was tested for its drug likeness and absorption, distribution, excertion, metabolism, and toxicology properties. The results revealed that the compound accepted the three rule out of four in Lipinski rule of five. ADME properties and toxicity of the phytocompound showed oral bioavailability which are under permissible limit. Conclusion: From the present investigation, it was proved that the phytocompound Stigmast – 5 – En - 3 Beta – Ol is harmless and effect potent against dental caries causing microbes.